Perbandingan Metode Saw Dan Topsis Dalam Pemilihan Tujuan Wisata Di Jawa Barat - Sunarti Sunarti (Techno.Com, 2019)
The activities of diverse, dense flurry of making people want to refresh eliminate tired from the busy daily routine. One way is to make a tour. Determine the purpose of there desirability is not easy. Prior to the goal, first seeking information about the area to be visited, then comparing and selecting the appropriate criteria. To assist visitors in finding a tourist holiday destination then it takes a computer-based system. This system can be used for decision making for tourist visitors to search for a tourist destination. The required criteria are the location, costs, transportation, distance, time of visit, and facilities. This study compares the author Saw and Topsis method, where that method showed results perangkingan not always the same because there is a different algorithm and value weighting scale differences. The purpose of this method is to help visitors who would tour the West Java in choosing the right attractions in accordance with his wishes. The research indicates that based on the method of Saw, the code (A3) with a value of 0.80 with the tourist attractions of the Park is designated as the primary option mekarsari on attractions in Indonesia. Whereas, the calculation using Topsis method in the code (A5) Goa Buniayu to the first option with a value of 0.59.